2017
DOI: 10.4172/2168-9547.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended Spectrum Beta Lactamase (ESBL) Producing Escherichia coli and Klebsiella pneumoniae Isolated from Raw Milk Samples in Al Jazirah State, Sudan

Abstract: Milk play a major role in human sources of nutrition and remain as the most important prominent in the Sudanese diet. Escherichia coli and Klebsiella pneumoniae are humans and animals opportunistic pathogens, responsible for a wide range of infections. The aim of this study was to evaluate the quality of the commercial available milk and to detect ESBL producing E. coli and K. pneumoniae from raw milk samples of cow in Al Jazirah state, Sudan. Seventy fresh row cow milk samples were collected and examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
7
20
3
Order By: Relevance
“…In this study, the majority of the E. coli isolates (65.3%) were found to be ESBL producers, a level similar to other studies [ 34 , 64 , 65 , 66 ] but higher than levels reported in Zambia (20%), Nigeria (37.8%), and Ghana (29%) [ 49 , 67 , 68 ]. All ESBL producers were significantly more resistant to all the tested antimicrobials as compared to the non-ESBL producers, suggesting selective pressure due to extensive use of beta-lactam and cephalosporin in animal farming, and the existence of multiple resistance mechanisms resulting from indiscriminate use of veterinary drugs [ 69 , 70 , 71 , 72 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the majority of the E. coli isolates (65.3%) were found to be ESBL producers, a level similar to other studies [ 34 , 64 , 65 , 66 ] but higher than levels reported in Zambia (20%), Nigeria (37.8%), and Ghana (29%) [ 49 , 67 , 68 ]. All ESBL producers were significantly more resistant to all the tested antimicrobials as compared to the non-ESBL producers, suggesting selective pressure due to extensive use of beta-lactam and cephalosporin in animal farming, and the existence of multiple resistance mechanisms resulting from indiscriminate use of veterinary drugs [ 69 , 70 , 71 , 72 ].…”
Section: Discussionsupporting
confidence: 88%
“…These high values were consistent with other reports on ESBL prevalence such as those from India and Egypt[34] [38] where ESBL production as high as 41.5% in E. coli, and 54.5% in K. pneumoniae were found. Values higher (91% in E. coli and 89.2% in K. pneumoniae) than observed in this study, have, however, been reported[45] in Aljazira State of Sudan. Much lower results compared to the result from the present finding of 32% in E. coli, 20% in K. pneumoniae, 20% in Proteus spp.…”
contrasting
confidence: 86%
“…Approximately 12% of the total milk samples screened were found to yield E. coli isolates in this study which were also supported by Kamaruzzaman [ 13 ], Badri et al . [ 14 ], Geser et al . [ 15 ], and Ali et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] reported 36 (23.53%) and Badri et al . [ 14 ] reported 29.3% ESBL-positive E. coli strains from bovine milk samples which may be of great concern as these pathogens may be carried out to the human consumers as well as calves leading to the spread of the antibiotic-resistant pathogens over human and animal population. Sharma et al .…”
Section: Discussionmentioning
confidence: 99%